2015
DOI: 10.1111/maps.12478
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to fireball modeling: The observable and the calculated

Abstract: Abstract-Estimating the mass of a meteoroid passing through the Earth's atmosphere is essential to determining potential meteorite fall positions. High-resolution fireball images from dedicated camera networks provide the position and timing for fireball bright flight trajectories. There are two established mass determination methods: the photometric and the dynamic. A new approach is proposed, based on the dynamic method. A dynamic optimization initially constrains unknown meteoroid characteristics which are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 17 publications
0
53
0
Order By: Relevance
“…enough to obtain meaningful results when the trajectory is shorter than 100 km. However, recent studies have shown that more satisfactory results can be obtained with the use of more rigorous methodologies [Sansom et al, 2015, Jansen-Sturgeon et al, 2019a. This is particularly true for a grazing fireball where the meteoroid is traveling hundreds to thousands of kilometers through the atmosphere.…”
Section: Triangulationmentioning
confidence: 99%
“…enough to obtain meaningful results when the trajectory is shorter than 100 km. However, recent studies have shown that more satisfactory results can be obtained with the use of more rigorous methodologies [Sansom et al, 2015, Jansen-Sturgeon et al, 2019a. This is particularly true for a grazing fireball where the meteoroid is traveling hundreds to thousands of kilometers through the atmosphere.…”
Section: Triangulationmentioning
confidence: 99%
“…Gritsevich et al (2012), where the few Taurids registered by the MORP are marked separately. Symbols for Pribram, Lost City, Innisfree, Neuschwanstein (Gritsevich 2008a), Benesov (Gritsevich 2008b;Gritsevich et al 2017) Park Forest (Meier et al 2017), Annama , Bunburra Rockhole (Sansom et al 2015), Kosice , and Dingle Dell (Devillepoix et al 2018) meteorites are also shown. Note that Innisfree and Annama show nearly the same α and β values and so their symbols coincide in the graph.…”
Section: Discussionmentioning
confidence: 99%
“…The relative timing along the bright flight trajectory provides the velocity information required to calculate a fall position probability distribution, while the precise absolute arrival time is required for the orbital calculation. Trajectory analysis and mass estimation are performed using the dynamic method detailed in Sansom et al (2015), giving a robust analysis of the observational and modeling errors involved. After the mass distribution has been estimated, dark flight modeling simulates the meteoroid behavior as it falls to the ground after ablation ceases and it is no longer visible to the camera network; the atmospheric conditions are modeled in the relevant volume from a climate model based on the best available local meteorological data including groundbased measurements and balloon flight data.…”
Section: Fireball Camera Networkmentioning
confidence: 99%
“…If the sequence rate is too high for a particular scenario, the elements (dashes) in the sequence will smear together making the decoding difficult or impossible. A sequence rate near the upper limit is desirable to provide as many trajectory timing data points as possible and therefore, a more accurate meteoroid mass estimationusing the dynamic method (Sansom et al 2015)-and fall position distribution. Faster meteors can be imaged with a higher sequence rate than slower meteors because each dash and blank of the meteor trail is projected across more pixels on the sensor making it easier to discern between the individual segments.…”
Section: Sequence Parameters For Fireball Observationmentioning
confidence: 99%